NO2 and children's respiratory symptoms in the PATY study. Issue 12 (29th November 2006) - Pattenden, S; Hoek, G; Braun-Fahrländer, C; Forastiere, F; Kosheleva, A; Neuberger, M; Fletcher, T
Abstract : Objectives: NO2 is a major urban air pollutant. Previously reported associations between ambient NO2 and children's respiratory health have been inconsistent, and independent effects of correlated pollutants hard to assess. The authors examined effects of NO2 on a spectrum of 11 respiratory symptoms, controlling for PM10 and SO2, using a large pooled dataset. Methods: Cross sectional studies were conducted in Russia, Austria, Italy, Switzerland, and the Netherlands, during 1993–99, contributing in total 23 955 children. Study-specific odds ratios for associations with ambient NO2 are estimated using logistic regressions with area-level random effects. Heterogeneity between study-specific results, and mean estimates (allowing for heterogeneity) are calculated. Results: Long term average NO2 concentrations were unrelated to prevalences of bronchitis or asthma. Associations were found for sensitivity to inhaled allergens and allergy to pets, with mean odds ratios around 1.14 per 10 μg/m 3 NO2 . SO2 had little confounding effect, but an initial association between NO2 and morning cough was reduced after controlling for PM10. Associations with reported allergy were not reduced by adjustment for the other pollutants. Odds ratios for allergic symptoms tended to be higher for the 9–12 year old children compared with the 6–8 year old children. Conclusions: Evidence for associations between NO2 and respiratory symptoms was robust only for inhalation allergies. NO2 most likely is acting as an indicator of traffic related air pollutants, though its direct effect cannot be ruled out. This remains important, as policies to reduce traffic related air pollution will not result in rapid reductions.